白首烏와 啤酒花 복합물의 에스트로겐 활성과 파골세포 분화 억제효과 - 박동준; Dongjun Park; 이홍구; Hong Gu Lee; 민경인; Kyoungin Min; 박형국; Hyoungkook Park; 진무현; Mu Hyun Jin; 조호성; Ho Song Cho (대한본초학회지(본초분과학회지), 2022)
Objectives : This study aimed to investigate the synergistic effect of combining Cynanchi Wilfordii Radix extract with Humuli Lupuli Flos extract on estrogenic and anti-osteoclastogenic activity. Methods : Estrogenic effect of a mixture of Cynanchi Wilfordii Radix extract and Humuli Lupuli Flos extract (CWHL), Cynanchi Wilfordii Radix extract, Humuli Lupuli Flos extract, caudatin (an active ingredient of Cynanchi wilfordii Radix extract) and 8-prenylnaringenin (an active ingredient of Humuli Lupuli Flos extract) were examined by proliferation E-screen assay and expression of estrogen inducible gene, pS2 via Real Time-PCR (RT-PCR) in MCF-7 estrogen responsive cells. And their estrogenic activities were investigated how to modulate Estrogen receptor β by binding affinity assay. Inhibitory effect of CWHL, Cynanchi Wilfordii Radix extract, Humuli Lupuli Flos extract, caudatin and 8-prenylnaringenin on RANKL-induced osteoclast differentiation were tested by TRAP (Tartrate-resistant acid phosphatase) staining in osteoclastogenic RAW 264.7 cells. Results : CWHL, Humuli Lupuli Flos extract and 8-prenylnaringenin accelerated the proliferation of MCF-7 and the expression of pS2 in MCF-7. CWHL, Cynanchi Wilfordii Radix extract, Humuli Lupuli Flos extract, caudatin and 8-prenylnaringenin bind to estrogen receptor β. CWHL, Cynanchi Wilfordii Radix extract, Humuli Lupuli Flos extract, caudatin and 8-prenylnaringenin inhibited RANKL-induced osteoclastogenesis in osteoclastogenic RAW 264.7. CWHL is more effective for all markers than Cynanchi Wilfordii Radix extract or Humuli Lupuli Flos extract alone. Conclusions : CWHL may a potential therapeutic agent for menopause and osteoporosis as a natural food resource. CWHL as a natural food source has therapeutic potential in cases of menopause and osteoporosis.